Dendrimer Based Formulation of Erlotiniib HCl: Development, Characterization and In-Vitro Evaluation - D. Singh, Rachna; Khare, Vaibhav; Yusuf, Farnaz; Hamid, Abid; Chaubey, Asha; Singh, Shashank (Pharmaceutical Nanotechnology, 2015)
Background: Erlotinib-HCl is a quinazoline derivative used as a first line drug in the treatment of advanced non-small-cell lung cancer. Conventionally, erlotinib HCl tablets has poor solubility in water and its dissolution is much lower in the fasting state as compared to the fed state. Oral absorption of erlotinib HCl is higher when administered with food. It is due to food which delays the gastric emptying time and allows more time for erlotinib HCl to exposes to fat in which it is more soluble. Thus, oral bioavailability of erlotinib HCl in fasting state has limitation in comparison to fed state, it affect the therapeutic efficacy of erlotinib HCl. Therefore, there is a need to improve art of delivery of erlotinib HCl which can overcome bioavailability issues. In the present study, we formulated dendrimers based formulation in order to improve its PK-PD profiles. Methods: Methods described in detail in the article for design and synthesis of Silica based Erlotinib dendrimer which was further evaluated mechanistically for bio efficacy and its toxicities. Results: The quinazoline dendrimer had an effective average particle size of about 100-1000 nm with drug loading efficiency of 0.571% and encapsulation efficiency was 38 %. In vitro cytotoxicity against panel of EGFR overexpressing cell line reveals lowest IC50 values 3.4 µM in A431 cell line, whereas 0.2 µM for NCI-H322 cell line. To assess the effect on DNA cell cycle by test material hypo diploid sub-G1 DNA fraction (<2n DNA) of the cells measured in treated cells using flowcytometer at 0.5, 1, 1.5 µM and was found to be 21.5, 15.4 and 17.2% respectively. The loss of mitochondrial membrane potential indicate it induces programmed cell death in cells via intrinsic pathway. Induction of genotoxic DNA damage indicate that dendrimer treated NCI-H322 cells resulted formation of comets with head DNA of 69.95 and 41.4% at concentration 0.5 and 1.5 µM respectively. Conclusion: In vitro results of dendrimer based nano scaled formulation showing promising results as compared to the free drug reveal that the formulation can further be evaluated for development as alternative delivery system.
Keywords: Dendrimer